A SWIFTLET HOUSE SECURITY SYSTEM BASED ON LONG-RANGE COMMUNICATION TECHNOLOGY AND THE INTERNET - akmal_zuhdi (Faculty of Engineering, Universitas Tanjungpura, 2026)
Swiftlet houses require a security system capable of real-time monitoring to reduce the risks of theft, fire, and environmental disturbances. This study aims to develop an Internet of Things (IoT)-based security system using LoRa RFM95 communication and the Thinger.io platform. The system employs an Arduino Uno with DHT22, MQ-2, flame, PIR, and infrared (IR) sensors to monitor environmental and security conditions. Sensor data are transmitted via LoRa to an ESP8266 receiver and displayed on the Thinger.io dashboard in real time. The test results show that all sensors operated properly and that LoRa communication reliably transmitted data over distances of up to 250 meters. The proposed system enables effective real-time monitoring and long-range communication for swallow bird house security.